A Concise Guide to the Bionomics and Key Morphological Characteristics for Identifying Culex coronator (Dyar & Knab, 1906) – an Invasive Mosquito Species from the Neotropics - Ana L. Romero-Weaver; Lawrence E. Reeves; Michael T. Riles; Yoosook Lee; Bryan V. Giordano (EDIS, 2023)
Culex coronator Dyar and Knab is a highly invasive Neotropical species, first described at the beginning of the 20th century in Trinidad and Tobago (Dyar and Knab 1906). This is an important invasive species in Florida, which needs to be carefully surveilled by mosquito control experts. This article is structured similar to those from Walter Reed Biosystematics Unit (WRBU) so that readers would obtain the similar level of details offered through WRBU species pages, which is widely used by anyone interested in mosquito biology, research, and education.